Child modern slavery, trafficking and health: a practical review of factors contributing to children's vulnerability and the potential impacts of severe exploitation on health - Laura C N Wood (BMJ Publishing Group, 2020)
Child trafficking is a form of modern slavery, a rapidly growing, mutating and multifaceted system of severe human exploitation, violence against children, child abuse and child rights violations. Modern slavery and human trafficking (MSHT) represents a major global public health concern with victims exposed to profound short-term and long-term physical, mental, psychological, developmental and even generational risks to health. Children with increased vulnerability to MSHT, victims (in active exploitation) and survivors (post-MSHT exploitation) are attending healthcare settings, presenting critical windows of opportunity for safeguarding and health intervention.Recognition of child modern slavery victims can be very challenging. Healthcare providers benefit from understanding the diversity of potential physical, mental, behavioural and developmental health presentations, and the complexity of children's responses to threat, fear, manipulation, deception and abuse.Healthcare professionals are also encouraged to have influence, where possible, beyond the care of individual patients. Research, health insights, advocacy and promotion of MSHT survivor input enhances the collaborative development of evidence-based approaches to prevention, intervention and aftercare of affected children and families.